Population pharmacokinetic of paracetamol and atorvastatin with co‐administration of semaglutide - Emilie K. Langeskov; Kim Kristensen (Wiley, 2022)
Abstract Semaglutide is a glucagon‐like‐peptide‐1 (GLP‐1) analogue marketed for once‐weekly subcutaneous administration for type 2 diabetes mellitus. Like other long‐acting GLP‐1 analogues, semaglutide reduces gastric emptying and, potentially, alters the rate of absorption of orally co‐administered drugs. The objective of the current analysis was to evaluate the effects on the gastric emptying rate caused by semaglutide on pharmacokinetic model parameters of paracetamol and atorvastatin in healthy subjects. Non‐linear mixed effect modeling was used to estimate population pharmacokinetic model parameters of paracetamol and atorvastatin after single doses with or without semaglutide. The absorption rate (ka) of paracetamol decreased by 53% when co‐administered with semaglutide. For atorvastatin, ka and transit compartment rate (ktr) decreased by 72% and 91%, respectively. Thus, gastric emptying, measured as T50, i.e., drug disappearance from the absorption compartments, showed an additional 5‐min delay for paracetamol and a 67‐min delay for atorvastatin when co‐administered with semaglutide. Semaglutide affected pharmacokinetic model parameters of paracetamol and atorvastatin, and minor quantitative differences in gastric emptying between placebo vs. semaglutide administration were observed. However, these effects of semaglutide were considered not to be of clinical relevance.